Insights into the control and consequences of breathing adjustments in fishes-from larvae to adults - Perry, Steve F.; Pan, Yihang K.; Gilmour, Kathleen M. (Frontiers in Physiology, 2023)
Adjustments of ventilation in fishes to regulate the volume of water flowing over the gills are critically important responses to match branchial gas transfer with metabolic needs and to defend homeostasis during environmental fluctuations in O2 and/or CO2 levels. In this focused review, we discuss the control and consequences of ventilatory adjustments in fish, briefly summarizing ventilatory responses to hypoxia and hypercapnia before describing the current state of knowledge of the chemoreceptor cells and molecular mechanisms involved in sensing O2 and CO2. We emphasize, where possible, insights gained from studies on early developmental stages. In particular, zebrafish (Danio rerio) larvae have emerged as an important model for investigating the molecular mechanisms of O2 and CO2 chemosensing as well as the central integration of chemosensory information. Their value stems, in part, from their amenability to genetic manipulation, which enables the creation of loss-of-function mutants, optogenetic manipulation, and the production of transgenic fish with specific genes linked to fluorescent reporters or biosensors.